Determination of cerebral blood flow velocity and microembolic signals in essential thrombocytosis by transcranial doppler ultrasonography. (1st February 2021) - Cinar, Ahmet; Cetin, Guven; Altintas Kadirhan, Ozge; Turgut, Seda; Ekinci, Iskender; Asil, Talip
ABSTRACT: Objectives: The goal of treatment in essential thrombocytosis (ET) is to prevent vascular complications such as thrombosis and hemorrhage. This study aimed to evaluate the risk of cerebrovascular microembolism in ET patients due to detection of microembolic signals (MES) and measure cerebral blood flow velocity (CBFV) by Transcranial Doppler (TCD) ultrasonography. Material and Methods: In this prospective case-control study, forty patients with diagnosed ET and age and sex-matched forty healthy controls were examined by the TCD sonography. Results: The ET group had a higher rate of MES (8/40) in the right MCA than that in the control group (none), as measured by TCD. Five patients had MES at the left MCA compared to that in no subjects in the control group. The comparison of the ET and control groups in terms of CBFV parameters showed significantly lower end-diastolic FV at the right MCA in the ET group compared to that in the control group (p < 0.05). On the other hand; both pulsatility and resistance indices in the right and left MCA and the ratios of systolic to diastolic blood flow rates in the right and left MCA were significantly higher in the ET group than that in the control group. Discussion: This study revealed that MES seems to be more common in patients with ET despite treatment. We could suggest that ET patients should be monitored more closely to address the potential risk of developing a cerebrovascular disease, which can be estimated by detection MES and raised CBFV, combine antiplatelet therapies to standard treatments.